GLOBAL SCENARIO IN PHARMACEUTICAL INDUSTRIAL AND ACADEMIC RESEARCH - Gspiar, (intellectual Property: Creation & Protection)â€ (Asian Journal of Pharmaceutical and Clinical Research, 2018)
ABSTRACT BOOK Organized by Faculty of Pharmacy, Dr. APJ Abdul Kalam University, Indore Published by Asian Journal of Pharmaceutical & Clinical Research (ISSN 2455-3891) www.ajpcr.com